Prevalence and Spectrum of Congenital Malformations in a Tertiary Care Centre - Tapan Pattanaik; Sunita Samal; Tanaya Jena (JCDR Research and Publications Pvt. Ltd., 2016)
Introduction: Congenital anomaly is an abnormality of physical structure that is seen at birth or within few weeks after. These abnormalities largely contribute to neonatal and infant morbidity and mortality. The occurrence and pattern of presentation vary from region to region. The exact aetiology is not known and genetic and environmental factors may be implicated. Aim: To determine the prevalence and types of congenital anomalies in newborns and to study the associated risk factors. Materials and Methods: This observational hospital based study was conducted in Department of Obstetrics and Gynaecology MKCG Medical College and Hospital, Berhampur, Odisha. Total 100 cases of congenital malformation detected antenatally or after delivery were analysed within a study period of Jan2011 to March 2012. Result: Total 100 cases of anomalies were studied out of 7973 pregnancies. The prevalence of congenital malformation was 125 in 1000(12.5%). Major congenital malformations were 104 in 1000(10.4%) and minor malformations were 21 in 1000(2.1%). Most of the anomalous babies were born to women of fourth gravida or more (42%). Commonest system involved was central nervous system (43%). In the postpartum period maximum (56%) babies were diagnosed to have anomalies. Amniotic fluid abnormalities were the most commonly (18%) associated maternal conditions. Conclusion: Congenital anomalies are important causes of still births and infant mortality, and are also contributors to childhood morbidity. Hence prenatal diagnosis by proper antenatal care and targeted scan is essential.